Pengaruh perbedaan persentase karagenan dan jumlah cairan terhadap tingkat kesukaan dan kandungan gizi pangan fungsional jelly stick selasih-rosela - Alya Hasna Fauziyah; Noor Rohmah Mayasari (ARGIPA (Arsip Gizi dan Pangan), 2026)
Dietary fiber-rich foods are still less considered in food choices of Indonesian people, as evidenced by the Indonesia Health Survey 2023, indicating that 96.7% consumed less than five servings of fruits and vegetables daily over the week. Inadequate dietary fiber intake has influenced changes in the disease patterns among Indonesians, with an increasing predominance of degenerative diseases along with lowering gastrointestinal health. Basil seeds-roselle jelly stick serves as an innovative approach that transforms fiber-rich food into convenient products that can be consumed in various settings. This product development aimed to determine the effects of carrageenan and liquid additions and their interaction on preference level based on hedonic parameters to identify the best formulation and its nutritional content. The design of this research is Completely Randomized Design with 2 factors: (1) carrageenan concentration (1,5%, 2%, 2,5%), (2) liquid volume (200g, 300g, 400g). Data were analyzed using two-way ANOVA followed by Duncan’s post hoc test. The result of this research indicated that variations in carrageenan concentrations affected the preference level for aroma and texture, different amounts of liquid affected preference level for color, taste, and texture, while the interaction between them affected taste preference. Formula F6, consisting of 2% carrageenan and 400g liquid, was selected as the best formulation and provides 2,39 g of carbohydrates; 0,49 g of fat; 2,74 g of protein; 2,73 g of dietary fiber; 0,44 g of soluble fiber; 2,29 g of insoluble fiber; 5,29 mg of vitamin C. This product supports adequate dietary fiber intake and is a low-fat functional food.